The Electric Power Generation from Horizontal Sea Wave Direction by Using Four Power Transmissions - ไชยชาญ, วีระศักดิ์; ไชยชาญ, วรรณวิภา (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2017)
This paper presents the electric power generation from horizontal sea wave direction by using four power transmissions. The purpose of this study is to increase the power output from horizontal wave direction. The researchers designed the four power transmissions that can move independently along the horizontal sea wave direction to push the shaft of gear box. Three-phase generator shaft is attached to the shaft of gear box can rotate and generate electricity. The AC power from the 3-phase generator will be converted to DC power by AC-DC converter to be able to supply power to DC power. This research was tested in the laboratory by simulating wave direction at frequencies of 0.17 Hz, 0.25 Hz and 0.5 Hz. The experimental results found that when installing 1, 2, 3 and 4 power transmissions, the maximum power of 69 W that generated from four power transmissions at sea wave frequency of 0.5 Hz.